293. Lung Cancer and Hematologic Malignancy ( HM) Patients Are Associated with the Highest Risk of Progressing to Severe Disease and Mortality in Cancer Patients with COVID-19. (4th December 2021) - Chaftari, Anne-Marie; Malek, Alexandre; Dagher, Hiba; Jiang, Ying; Bayle, Arnaud; Bhinder, Arvinder; Cruz, Ana Fernandez; Siddiqui, Bilal; Somer, Robert; Datoguia, Tarcila; Slavin, Monica; Dragvich, Tomislav; et al.
Abstract: Background: Several studies have shown that underlying cancer is a risk factor for progression of COVID-19 to severe illness and fatal outcome but there is very little data that specifies which underlying cancer puts this patient population at the highest risk. Methods: We retrospectively collected de-identified data on 1115 cancer patients diagnosed with COVID-19 between January and November 2020, at 12 centers in Asia, Australia, Europe, North America, and South America. Patient characteristics including age, type of malignancy (hematologic malignancy [HM], lung cancer, and non-lung cancer were determined in association with severe illness as well as all-cause mortality within 30 days after COVID-19 diagnosis. Results: By multivariable logistic regression analysis, independent risk factors for 30-day mortality in cancer patients included age > 65 (OR 6.64; 95% CI 3.351to 12.55; p< 0.0001), ALC < 0.5 K/microliter (OR 2.10; 95% CI 1.16 to 3.79; p=0.014), and anemia at < 10g/dl (OR 2.41; 95% CI 1.30 to 4.44; p=0.005). Among cancer patients, the 30-day mortality rate was significantly higher in patients with lung cancer than in patients with non-lung cancer solid tumors, including those with lung metastases (22% vs 9%; p=0.001). Patients with HM tended to have higher 30-day mortality than patients with non-lung cancer solid tumors (13% vs 9% p=0.07) and tended to have a lower mortality rate than patients with lung cancer (p=0.07). Furthermore, HM patients were more likely to be lymphopenic and anemic at diagnosis as well as progress to LRTI and be placed on ventilatory support compared to non-lung cancer solid tumor patients ( p= or < 0.01). In addition, lung cancer and HM patients were more likely to develop hypoxia and require hospital admission than non-lung cancer solid tumor patients ( p=0.01). Conclusion: Lung cancer and HM patients are associated with the highest risk of progressing to severe disease and mortality in cancer patients with COVID-19. Hence, cancer patient population should be given the highest priority as far as prevention [vaccination with boosters if needed] as well as preemptive early therapy with monoclonal antibodies right after the onset of COVID-19. Disclosures: Monica Slavin, MBBS, MD, F2G (Advisor or Review Panel member)Merck (Advisor or Review Panel member)Pfizer (Advisor or Review Panel member)